PERAN GURU DALAM PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS DI KELAS 1 SDN 74 PALEMBANG - Devi Kumalasari; Muhsana El Cintami Lanos, Bambang Hermansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of teachers in the learning of children with special needs (ABK) in class 1 of SDN 74 Palembang. The background of this study is based on the importance of the role of teachers in realizing inclusive education that is able to meet the learning needs of each student, including children with special needs. This study uses a descriptive qualitative approach. Data collection techniques are carried out through direct observation in class, in-depth interviews with teachers, documentation of learning activities, and distribution of questionnaires to class teachers. The results of the study indicate that teachers act as facilitators, guides, and class managers in the ABK learning process. Teachers show high empathy and concern, and try to adjust learning strategies to suit student needs. However, the study also found several obstacles such as limited knowledge about individual approaches, minimal special training, and limited supporting facilities. These findings indicate that even though teachers have made maximum efforts, training and facility support are still needed to optimize the implementation of inclusive education.